From workers to trade unionists: Transformation and instrumentalism in workers and adult education after the First World War - Fred M. Schied (Adult Education Research Conference, 1994)
This paper traces the movement from workers' education for social transformation to a more accommodative form of education. It argues that the dispute between progressive elements and the business trade union faction centered on control over the Workers Education Bureau.